THE PLURALITY OF RELIGIOUS EDUCATION IN ISLAM PESANTREN DDI UJUNG LARE KOTA PAREPARE - Herda, Abdul Rauf Ibrahim (IAIN Ambon, 2019)
learning resources developed at pondok pesantren during this time oriented plurality. Good learning material PAI as well as religious tradition that held through extracurricular activities and kokurikuler are always paying attention to the teaching of the equation, the equation, the fraternity and compassion in Islam. Typology of religious learning resources that are rooted in Pesantren Putri DDI Lil Banat is an understanding of the religion institution of moderate, tolerant and inklusivisme. Pesantren as a religious educational institutions often compromised the spread understand religious radicalism. From this aspect, if the existence of boarding school instrumental more urgency in developing the views, attitudes towards the plurality of values.